Ascl1 and OTP tumour expressions are associated with disease‐free survival in lung atypical carcinoids. Issue 6 (21st February 2023) - Centonze, Giovanni; Maisonneuve, Patrick; Simbolo, Michele; Lagano, Vincenzo; Grillo, Federica; Prinzi, Natalie; Pusceddu, Sara; Missiato, Loretta; Colantuono, Marilena; Sabella, Giovanna; Bercich, Luisa; Mangogna, Alessandro; et al.
Aims: According to World Health Organization guidelines, atypical carcinoids (ACs) are well‐differentiated lung neuroendocrine tumours with 2–10 mitoses/2 mm 2 and/or foci of necrosis (usually punctate). Besides morphological criteria, no further tools in predicting AC clinical outcomes are proposed. The aim of this work was to identify novel factors able to predict AC disease aggressiveness and progression. Methods and results: Three hundred‐seventy lung carcinoids were collected and centrally reviewed by two expert pathologists. Morphology and immunohistochemical markers (Ki‐67, TTF‐1, CD44, OTP, SSTR2A, Ascl1, p53, and Rb1) were studied and correlated with disease‐free survival (DFS) and overall survival (OS). Fifty‐eight of 370 tumours were defined as AC. Survival analysis showed that patients with Ascl1 + ACs and those with OTP‐ACs had a significantly worse DFS than patients with Ascl1‐ACs and OTP + ACs, respectively. Combining Ascl1 and OTP expressions, groups were formed reflecting the aggressiveness of disease ( P = 0.0005). Ki‐67 ≥10% patients had a significantly worse DFS than patients with Ki‐67 <10%. At multivariable analysis, Ascl1 (present versus absent, hazard ratio [HR] = 3.42, 95% confidence interval [CI] 1.35–8.65, P = 0.009) and OTP (present versus absent, HR = 0.26, 95% CI 0.10–0.68, P = 0.006) were independently associated with DFS. The prognosis of patients with Ki‐67 ≥10% tended to be worse compared to that with Ki‐67 <10%. On the contrary, OTP (present versus absent, HR = 0.28, 95% CI 0.09–0.89, P = 0.03), tumour stage (III‐IV versus I‐II, HR = 4.25, 95% CI 1.42–12.73, P = 0.01) and increasing age (10‐year increase, HR = 1.67, 95% CI 1.04–2.68, P = 0.03) were independently associated with OS. Conclusion: This retrospective analysis of lung ACs showed that Ascl1 and OTP could be the main prognostic drivers of postoperative recurrence. Abstract : Ascl1, OTP, and Ki‐67 drive the clinical outcome of lung atypical carcinoids.